Effect of pharmaceutical care interventions on glycemic control in patients with diabetes: a systematic review and meta-analysis - Jeong S; Lee M; Ji E (Dove Medical Press, 2018)
Sohyun Jeong, Minhee Lee, Eunhee Ji College of Pharmacy and Research Institute of Pharmaceutical Sciences, Gachon University, Incheon, Republic of Korea Purpose: Diabetes is a chronic lifelong condition, and adherence to medications and self-monitoring of blood glucose are challenging for diabetic patients. The dramatic increase in the prevalence of diabetes is largely due to the incidence of type 2 diabetes in low- and middle-income countries (LMIc) besides high-income countries (HIc). We aimed to evaluate whether pharmacist care (PC) service model in LMIc and HIc could improve clinical outcomes in diabetic patients by performing a meta-analysis. Methods: PubMed, Embase, and ProQuest Dissertations Unlimited Published Literature database were searched to find publications pertaining to pharmacist-led intervention in patients with diabetes. The inclusion criteria were as follows: 1) randomized controlled trials, 2) confirmed diabetic patients (type 1 or type 2), 3) pharmaceutical care intervention by clinical pharmacist or/and multidisciplinary team, and 4) reporting HbA1c at baseline and end of study or the mean change in these values. Results: A total of 37 articles were included in the meta-analysis. The overall result was significant and in favor of PC intervention on HbA1c change (standard difference in mean values [SDM]: 0.379, 95% CI: 0.208–0.550, P<0.001). The stratified meta-analysis showed that PC was significant in both HIc (n=20; SDM: 0.351, 95% CI: 0.207–0.495) and LMIc (n=15; SDM: 0.426, 95% CI: 0.071–0.780). More than 6 months is needed to obtain adequate effects on clinical diabetes parameters. Conclusion: Our study presented that an adequate duration of pharmacist-led pharmaceutical care was effective in improving HbA1c in patients with diabetes in both LMIc and HIc. Keywords: pharmacist care, multidisciplinary team care, diabetes, high-income country, low- and middle-income country